A semi-tethered swimming test better predicts maximal swimming velocity if drag force is considered - Soncin, R.; Szmuchrowski, L. A.; Oliveira Claudino, J. G.; Ferreira, J. C.; Pinho, J.; Vilas-Boas, J. P.; Amadio, C.; Huebner, R.; Serrão, J. C.; Mezêncio, B. (Revista Portuguesa de Ciências do Desporto, 2021)
Semi-tethered swimming is a method used to evaluate the propulsive forces generated by swimmers and could be performed using a load cell while the participant swims at a constant and controlled velocity. Usually, the correlation between semi-tethered force and swimming maximal velocity is lower than the value observed for fully tethered swimming, probably due to the propulsive force necessary to overcome the drag during the test usually disregarded on the models. The aim of the current study was to examine the relation between semi-tethered swimming force and swimming mean velocity while considering the necessary force for swimmers to overcome the hydrodynamic drag. Twelve experienced front crawl swimmers performed five maximal 25m swim trials and five trials of semi-tethered swimming. Data correlation was evaluated by a non-linear model based on both the mean propulsive force and the mean velocity during the semi-tethered test. The linear regression between the mean swimming velocity and the mean semi-tethered force showed an r2= .597 and a higher value (r2= .900) when the force to overcome the drag was considered. The high correlation coefficient found between the mean semi-tethered force (considering the force to overcome the drag) and the mean swimming velocity suggests that this force could be more suitable for practical purposes.